The role of mathematics in transdisciplinarity content of modern education - V. A. Testov; E. A. Perminov (Russian State Vocational Pedagogical University, 2021)
Introduction. In the context of modernisation in modern education, a deeper (by contrast to interdisciplinary) transdisciplinary level of cognition is becoming prevalent. Transdisciplinary level generates a universal methodology capable of addressing the complex multi-factorial interdisciplinary problems of nature and society. The result is transdisciplinary branches of science such as cybernetics, disaster theory, synergetics, artificial intelligence, big data, etc. All these concepts have been developed on the basis of the achievements of mathematics over the past 70-80 years, the era of mathematical sciences. As a consequence, mathematics has become the basis of the language of information technologies and processes, and, thereby, this science has given rise to a global digital transformation of society based on the use of the unique computer capabilities.The aim of the present research was to explore the role of mathematics in the transdisciplinary trend in updating the content of education with a view to bringing education to a higher (by contrast to interdisciplinary) level, based on the inclusion of modern mathematical theories and methods in the content of education and their applications depending on the direction and profile of the student training.Methodology and research methods. In the course of research, the systemic, cultural, and meta-subject approaches were employed to analyse the role of mathematics in education and to solve the transdisciplinary problems of education content modernisation (based on the most striking manifestations of modern mathematical culture). As a result of the synthesis of these approaches, a holistic scientific worldview emerges, which not only goes beyond the traditional disciplines and methods, but also appears above them.Results and scientific novelty. The analysis of transdisciplinary trend in postindustrial education was carried out. Mathematical and pedagogical aspects of the implementation of systemic, cultural and meta-subject approaches were investigated in order to achieve a higher level of educational process. At the same time, the authors justified the use of mathematical modelling, discrete mathematics, computational processes and artificial intelligence in the training, i.e. formation of a new superdisciplinary way of thinking in students, acquisition of a general cultural cognitive strategy to perform professional and transprofessional tasks.Practical importance. The findings of the current publication contribute to the realisation of the transdisciplinary trend in the content of student training, and will be of interest to both educational theorists and teachers, who train students in many fields. Moreover, this work will be useful for all those interested in the future advancement of the system of education.